A STUDY OF IMPORTANCE OF ETHICS ANDSOCIAL RESPONSIBILITY: A SYUDY OF MARKETING PROFESTIONAL - kalita, Dr. Jyoti Prasad (The journal of contemporary issues in business and government, 2021)
In this topic I am briefing the topic of business ethics. The free market economy which is mostly suited for the community is being threatened by the way of a certain theories of business ethics.We can take an example from the recent book by Joseph W. Weiss, Business Ethics, A Stakeholder and Issue Management Approach 3. It treats the stakeholder approach without any condition as the proper ethics for managers of business enterprises.It rejects the idea that who own a business have a moral right to have it managed, so to provide them with return on investment. "Critical" and "structured" parts of those definitions are both important and it is meant to be used in business ethics courses: Ethics in "Critical" in the mode of critiquing various moral beliefs and practices and examining. In other words, it’s not only decribe the people’s behaviour or value, which can be useful in starting point. Ethics involve to looking at the norms and behaviours and judging them, and examine that whether various values and norms are in contradiction mutually and asking which matters the most in what sort of Ethics is “Structured” in the sense that it is not only making an opinion about people how should they have to behave. Opinions can be made by anyone and Ethics involves using least attempts, to find higher-order, theories and principles in an attempt to unify and rationalize our diverse moral believe. For practical purpose, ethics stands for providing reasoned justification for our behaviour and choices when it affects others for our praise or criticism. “Business Ethics” can be defind as the detailed examination of the people and organisation that how should they behave in the corporate